A war too far? : Bush, Iraq, and the 2004 U.S. Presidential Election - Mac Allister, Ian (2006)
Contiene bibliografía
Keywords: 2004; Elecciones presidenciales; Comportamiento electoral; Irak; Estados Unidos; Guerra